Semantic Perspectives on Connotative Meaning in Robert Frost’s Poem "A Cliff Dwelling" - Firma Pradesta Amanah; Lianasari; Oktodila, Hasbi Thaufik; Syafrizal Azzali (Global Expert: Jurnal Bahasa dan Sastra, 2025)
Poetry, as a form of literary art, embodies the author’s imaginative expression and conceals layers of implied meaning beneath its surface. Its linguistic and stylistic complexity demands in-depth analysis to uncover the richness of its content. This study focuses on Robert Frost’s poem A Cliff Dwelling, which encapsulates profound and intricate connotative meanings. Previous studies on Frost’s works have predominantly explored thematic, stylistic, or symbolic aspects, yet few have investigated the semantic dimension of connotative meaning within his poetry, particularly in A Cliff Dwelling. This limited attention leaves a gap in understanding how semantic analysis can uncover deeper layers of interpretation in Frost’s linguistic choices and artistic expression. Investigating the connotative meanings in this poem is significant because they reveal how Frost uses language to portray the relationship between humanity and nature, the endurance of early civilization, and the transience of human existence—central themes that define his poetic vision. Employing a semantic approach, this research aims to identify and interpret the connotative meanings embedded in the poem and to uncover the multiple layers of interpretation it conveys. Leech’s (1981) theory of connotative meaning and aspects of meaning serve as the theoretical foundation of this study. Using a qualitative descriptive method, the analysis presents data in the form of words and interpretive descriptions. The findings indicate that connotative meaning encompasses the associative and emotional dimensions of words, shaped by the cultural perceptions and psychological responses of both the writer and the reader. These meanings, as reflected in Frost’s poem, portray human experiences and existential struggles expressed through poetic imagery. This study contributes to a deeper understanding of the semantic richness of Frost’s poetry and offers insights into his worldview and artistic vision. Keywords: A Cliff Dwelling, Connotative Meaning, Poetry Analysis, Robert Frost, Semantic Analysis